PENERAPAN GENIUS LEARNING DALAM MENINGKATKAN KEMAMPUAN MENULIS ESSAY SEJARAH SISWA KELAS XI SMAN 2 KS CILEGON - Ika Faika, Sri; Ruhiat, Yayat; Atikah, Cucu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study examines the effects of the Genius Learning teaching methodology and learning motivation on the ability of students in Grade XI SMAN 2 KS in Cilegon to write academic essays. Genius Learning is an educational methodology that aims to create and strengthen a positive and constructive learning environment. This condition is a warning sign that the learning outcome will be below average. Within this teaching approach, the instructor must convey to students that the classroom is a place that values them as human beings who are capable of learning and who, in turn, are held to a certain standard.Utilizing the potential for improving the quality of academic writing, this study aims to analyze the effectiveness of using the Genius Learning method to develop analytical, synthesis, and student evaluation skills. The qualitative research method uses observations of SMAN 2 Cilegon students in grades XI as the subject and study location. The research findings indicate that the implementation of the Genius Learning method significantly improves students' ability to write essays in class by increasing their critical and creative thinking skills. However, challenges like student adaptation to new methods and technological advancements are obstacles that must be overcome. It is recommended to do intensive training for teachers, enhance technological capabilities, develop accurate assessment tools, and provide students with encouragement to improve the effectiveness of this method.